Rhythm sensitivity in macaque monkeys - Selezneva, Elena; Deike, Susann; Knyazeva, Stanislava; Scheich, Henning; Brechmann, André; Brosch, Michael (Frontiers in Systems Neuroscience, 2013)
This study provides evidence that monkeys are rhythm sensitive. We composed isochronous tone sequences consisting of repeating triplets of two short tones and one long tone which humans perceive as repeating triplets of two weak and one strong beat. This regular sequence was compared to an irregular sequence with the same number of randomly arranged short and long tones with no such beat structure. To search for indication of rhythm sensitivity we employed an oddball paradigm in which occasional duration deviants were introduced in the sequences. In a pilot study on humans we showed that subjects more easily detected these deviants when they occurred in a regular sequence. In the monkeys we searched for spontaneous behaviors the animals executed concomitant with the deviants. We found that monkeys more frequently exhibited changes of gaze and facial expressions to the deviants when they occurred in the regular sequence compared to the irregular sequence. In addition we recorded neuronal firing and local field potentials from 175 sites of the primary auditory cortex during sequence presentation. We found that both types of neuronal signals differentiated regular from irregular sequences. Both signals were stronger in regular sequences and occurred after the onset of the long tones, i.e., at the position of the strong beat. Local field potential responses were also significantly larger for the durational deviants in regular sequences, yet in a later time window. We speculate that these temporal pattern-selective mechanisms with a focus on strong beats and their deviants underlie the perception of rhythm in the chosen sequences.